Pierwsza polka - Bienek, Horst, 1930-1990.; Bienek, Horst, 1930-1990. (Warszawa : Czytelnik, 1983)
The novel takes place in one day, August 31, 1939, and ends on September 1, 1939, when the Nazis attacked Poland.
Translation of: Die erste Polka.
Keywords: World War, 1939-1945 -- Germany -- Fiction